Applying Classical Control Theory to Energy-Economics Modeling—A Tool to Explain Model Behavior in Response to Varied Policy Decisions and Changing Inputs - Mar, B. W.; Bakken, O. A. (Management Science, 1981)
Classical control theory is applied to the field of energy-economics using the Dartmount model COAL as an illustration. Control theory can assist in establishing the credibility of existing energy-economic systems models, since it presents a better understanding of model response. The application of these models requires a translation of DYNAMO type conventions into differential equations and flow diagram usually used for control system analysis. The response of the model to parameter changes and model inputs can become routine analyses using classical control theory methodology. In the case of the COAL model it was shown that the model output does not experience detectable oscillations even when input oscillations are introduced. The model as formulated represents a well damped system, which may not be what the authors expected in their representation of the real system.